Data-Driven Decision-Making in Schools: Lessons from Trinidad - Yamin-Ali, Jennifer; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Yamin-Ali shows how schools can undertake responsible decision-making through gathering and evaluating data, using as examples six fully developed case studies that shed light on common questions of school culture and student life, including student stress, subject selection, and the role of single-sex classes.
Keywords: Science; Science; Science, general